2016
DOI: 10.1016/j.ijsu.2016.02.047
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes in patients with intraoperative Electrocorticography (EcoG) guided epilepsy surgery-experiences of a tertiary care centre in India

Abstract: The success of epilepsy surgery depends upon accurate localization and complete resection of the epileptogenic tissue, both of which are aided by intraoperative EcoG.Thus, intraoperative EcoG is a useful adjunct in epilepsy surgery to achieve optimal seizure freedom in cases of MTS plus, focal cortical dysplasia and tumors. Even the patients who are not seizure free can achieve worthwhile improvement post surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…The primary reason for poor surgical outcomes in patients with FCD is the inaccurate localization of the epileptogenic margins. These results further support that EcoG-guided resection is likely to have a better outcome in terms of achieving seizure freedom post-operatively [ 22 , 101 ].…”
Section: Discussionsupporting
confidence: 61%
“…The primary reason for poor surgical outcomes in patients with FCD is the inaccurate localization of the epileptogenic margins. These results further support that EcoG-guided resection is likely to have a better outcome in terms of achieving seizure freedom post-operatively [ 22 , 101 ].…”
Section: Discussionsupporting
confidence: 61%
“…Both can be achieved effectively after implementing intraoperative ECoG. In another study, it was observed that epileptic patients that were undergoing intraoperative ECoG-guided epileptic surgery demonstrated an improved post-surgical outcome, compared to patients getting normal or non-guided epileptic surgery [ 16 ]. Extraoperative ECoG can also be very useful in non-surgical epileptic treatments to identify the epileptic foci and to track the disease progression.…”
Section: Diagnostic Techniquesmentioning
confidence: 99%
“…Typically the electrodes are made of platinum [25][26][27] and are placed on the surface of the cortex [28]. Ravat et al [29] studied the potential use of ECoG for the diagnosis and therapy of epilepsy [30] and concluded that the success of an Epileptic surgery depends on the accurate localization and removal of the epileptogenic tissue [29]. Rosenow defined the epileptogenic zone as the area of the cortex indispensable for the generation of clinical seizures [31].…”
Section: Uses Of Ecog and Epilepsymentioning
confidence: 99%